Fate of transgenic DNA from orally administered Bt MON810 maize and effects on immune response and growth in pigs. - Maria C Walsh (Public Library of Science (PLoS), 2011)
We assessed the effect of short-term feeding of genetically modified (GM: Bt MON810) maize on immune responses and growth in weanling pigs and determined the fate of the transgenic DNA and protein in-vivo. Pigs were fed a diet containing 38.9% GM or non-GM isogenic parent line maize for 31 days. We observed that IL-12 and IFNγ production from mitogenic stimulated peripheral blood mononuclear cells decreased (P<0.10) following 31 days of GM maize exposure. While Cry1Ab-specific IgG and IgA were not detected in the plasma of GM maize-fed pigs, the detection of the cry1Ab gene and protein was limited to the gastrointestinal digesta and was not found in the kidneys, liver, spleen, muscle, heart or blood. Feeding GM maize to weanling pigs had no effect on growth performance or body weight. IL-6 and IL-4 production from isolated splenocytes were increased (P<0.05) in response to feeding GM maize while the proportion of CD4(+) T cells in the spleen decreased. In the ileum, the proportion of B cells and macrophages decreased while the proportion of CD4(+) T cells increased in GM maize-fed pigs. IL-8 and IL-4 production from isolated intraepithelial and lamina propria lymphocytes were also increased (P<0.05) in response to feeding GM maize. In conclusion, there was no evidence of cry1Ab gene or protein translocation to the organs and blood of weaning pigs. The growth of pigs was not affected by feeding GM maize. Alterations in immune responses were detected; however, their biologic relevance is questionable.